The Role of The Curricula of History in Building Human Thought. (Journal of Hama University, 2020)
This research aims to shed light on the curricula of history in general and the role of the curricula of history in building human thought.It is an attempt to explain that history the history of reason , creativity and thought and not necessarily that history of wars, disasters and woes .This innovation and inventions of ancient civilization have benefited from successive civilizations in the arts , architecture, medicine, and other fields.Thus, it is the product of human society as a whole for the good of all humanity.And how the curricula of history in Syria provide our students with this right understanding of the meaning of history , and that this understanding is an essential matter for realizing the meaning of history.Thus learning lessons and avoiding disasters and wars and searching for ways of rapprochement and dialogue with civilizations, not far from them, rivalries each other because of wars.